Prediction of shoreline change using a new long-term shoreline evolution model based on the concept of sediment balance - Ali, Omar; Ab Razak, Mohd Shahrizal (Penerbit UTM Press, 2022)
A new model that can predict long-term shoreline evolution in response to climate change for the 21st century has been developed. The developed model is an analytical model, capable of simulating coastal processes that contribute to long-term shoreline change, driven by the concept of sediment mass balance. The model was employed to simulate shoreline change along the 53 Km of coastline on the east coast of Peninsular Malaysia, which includes a variety of beach settings. The model was able to produce results close to the actual historical shoreline change for a hindcast period of 10 years, with an accuracy of 90%, indicating an excellent agreement between observed and predicted shoreline changes. Future coastal evolution predicted by the model indicate that by the year 2100, on average, 65% of beaches that are located along the coast of Pahang are going to disappear completely. Primarily due to the effects of long-term coastal sediment misbalance, the beaches are expected to lose roughly twice the amount of gained sediment as a result of the increasing impact of the coastal processes in the next 80 years.